Multibeam bathymetry raw data (Atlas Hydrosweep DS echo sounder entire dataset) of RV SONNE during cruise SO97/1 - Suess, Erwin; Wölfl, Anne-Cathrin (PANGAEA, 2023)
Multibeam bathymetry raw data was recorded in the North Pacific during cruise SO97/1 that took place between 1994-07-27 and 1994-08-23. The data was collected using the ship's own Atlas Hydrosweep DS echo sounder.